(untitled) (South East Asia Journal of Public Health, 2014)
Family planning programs are considered to be an important way to control the rapid population growth of Bangla-desh with the main focus being women. As a male dominant country, the knowledge of, attitude towards, and ap-proval of family planning is largely influenced by the male member of couples in their choice of appropriate contra-ceptive methods. This paper examined the determinants of current choices in family planning methods in relation to male knowledge, attitude and approval of family planning practices in Bangladesh. A total of 430 married men aged 15-49 years were interviewed in Narsingdi, a district town of Bangladesh. The findings revealed that the mens level of contraceptive knowledge and their attitude to modern contraceptive was high in this area. The findings asserted that the contraceptive prevalence rate among couples was (62.1%), with oral pills (26.51%) and withdrawals (6.25%) being the most preferred modern and traditional methods respectively. The multinomial logistic regression model has been applied to understand the determinants of the choice of contraceptive method. These findings indi-cated that women in skilled occupation, positive attitude towards modern contraceptives of male, high level of knowledge on contraceptive methods of male, approval of family planning by male, and current living children had significantly more positive effects on using modern contraceptives by the couple. It was also found that couples who desired more children were less likely to use modern contraceptives. Alternatively, the education level of the hus-band and the desired number of additional children had a negative impact on the use of traditional methods while media exposure, a high level of knowledge on contraceptives, and an approval of family planning had positive im-pacts on the use of traditional contraceptives over not using any method. The government should increase the fund-ing and availability of family planning programs which promote the use of modern contraceptive methods, espe-cially those that are targeted towards the male population. South East Asia Journal of Public Health 2013; 3(1): 50-56 DOI: http://dx.doi.org/10.3329/seajph.v3i1.17711